2017
DOI: 10.1016/j.biocon.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Identifying thresholds of logging intensity on dung beetle communities to improve the sustainable management of Amazonian tropical forests

Abstract: Selective logging is the most widespread driver of tropical forest disturbance. As such, it is critically important to identify at which spatial scale logging intensity should be measured and whether there are clear thresholds in the relationship between logging intensity and its impacts on biodiversity or ecological processes. We address this using a robust beforeand-after logging experimental design in the Brazilian Amazon, using a gradient of logging intensity measured at two different spatial scales. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 70 publications
2
30
2
1
Order By: Relevance
“…GAMs have been widely applied to investigate nonlinear relationships between dependent and non-explanatory variables in various fields of study such as plant and aquatic ecology (e.g., [58]) and water quality (e.g., [59]), as well as for nonlinear relationships among biotic and bon-biotic variables in environmental settings due to complex interactions between environmental factors. Many studies have identified nonlinear relationships among components of forest ecosystems (e.g., [3,50,[60][61][62][63][64][65]). In particular, Lee et al [3] reported that burn severity might be related to topographic characteristics such as elevation and slope.…”
Section: Linear and Nonlinear Model Estimationmentioning
confidence: 99%
“…GAMs have been widely applied to investigate nonlinear relationships between dependent and non-explanatory variables in various fields of study such as plant and aquatic ecology (e.g., [58]) and water quality (e.g., [59]), as well as for nonlinear relationships among biotic and bon-biotic variables in environmental settings due to complex interactions between environmental factors. Many studies have identified nonlinear relationships among components of forest ecosystems (e.g., [3,50,[60][61][62][63][64][65]). In particular, Lee et al [3] reported that burn severity might be related to topographic characteristics such as elevation and slope.…”
Section: Linear and Nonlinear Model Estimationmentioning
confidence: 99%
“…Harvesting natural tropical rainforest with selective cutting systems for timber production is the greatest driver of forest disturbance (Willot et al 2000;Franca et al 2017), which affects rainforest biodiversity and has disrupted the ecosystem processes (Barlow et al 2007;Ewers et al 2015). Logging causes significant shifts in community composition, distribution, and abundance of species (Edwards et al 2012;Franca et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Forest openness affects the abundance and species richness of invertebrates (Koivula and Niemela 2003;Thorn et al 2016). For example, sensitive dung beetle species may be lost following even low cutting intensity (Franca et al 2017). Natural tropical rainforest in eastern Borneo, Indonesia, has been logged with selective cutting system since 1970.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using Landsat data to map and quantify selective logging at lower logging intensities (< 20 m 3 ha -1 ) remains a major challenge, and the amount of forest disturbance overlooked using currently available techniques is unknown. Yet, growing concerns over the impacts of selective logging on carbon and biodiversity (Bicknell et al, 2014;Edwards et al, 2014;França et al, 2017;Martin et al, 2015;Putz et al, 2008) has led to increased use of improved forest management practices, such as reducedimpact logging (Putz and Pinard, 1993). Consequently, the extent of tropical forests being logged at lower intensities and with reduced-impact is almost certainly expanding.…”
Section: Introductionmentioning
confidence: 99%